A Framework for Deciding How to Create and Evaluate Transcripts for Forensic and Other Purposes - Fraser, Helen (Frontiers in Communication, 2022)
Transcripts are used successfully in many areas of contemporary society. However some uses of transcripts show systemic problems, with significant negative consequences. The key to finding effective solutions in these areas is to determine which factors contribute most strongly to the problems – which may be different from those to which they are most commonly ascribed. This paper offers a conceptual framework for understanding the nature of transcripts in general, and the factors that contribute to their reliability and suitability for purpose. It then demonstrates how the framework can explain the successful use of transcripts in two domains: court proceedings and linguistics research. Next, it uses the framework to examine two problematic cases: transcripts of forensic audio used as evidence in criminal trials, and transcripts of police interviews with suspects. A crucial observation is that, while it is common, and understandable, to focus on the transcriber as the source of problems with transcripts, transcription is actually a complex process involving practitioners in multiple roles, of which the transcriber role is not always the most important. Solving problems thus requires coordination of a range of factors. The analysis ends with practical suggestions for how to seek solutions for both of the problematic areas reviewed, with attention to the role that linguistic science needs to play. The conclusion amplifies recent calls to consolidate transcription as a dedicated field of study within linguistics.